تقييم ممارسات القيادة الإدارية في ظل الفكر الإداري الحديث-دراسة حالة مديرية التربية بولاية الوادي - صباح قطاوي; عواطف قطاوي; مديحة هقي (university of eloued جامعة الوادي, 2024)
هدفت الدراسة الي التعرف على أثر الممارسات القيادة الإدارية في ظل الفكر الإداري الحديث لدى عاملين مديرية التربية لولاية الوادي وتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي التحليلي كونه الأقرب إلى الأمام بكافة جوانب الدراسة من خلال التطرق إلى المفاهيم النظرية للقيادة الإدارية تعريفها ، أسسها وأنماطها ، أما المفاهيم التطبيقية تم اعدادها بواسطة استمارة الاستبيان مكونة من محورين ( أنماط القيادة والأداء) وزعت على 60 عاملا وتحليل نتائجها بواسطة برنامج spss , ومن أهم النتائج المتوصل إليها وجدنا من خلالها أن هناك علاقة ذات دلالة إحصائية بين المتغيرات المستقلة والمتمثلة في أنماط القيادة الإدارية والمتغير التابع وهو تقييم الأداء أما فرضية الفرق فوجدنا أنه لا توجد أي فروقات بين متوسطات اجابات العينة على محور أنماط القيادة الإدارية ومحور تقييم الأداء تعزى للمعلومات الشخصية. "The study aimed to identify the impact of administrative leadership practices in light of modern administrative thought among employees of the Directorate of Education for the State of El Oued. To achieve the objectives of the study, reliance was placed on the descriptive and analytical approach as it is the closest to the future in all aspects of the study by addressing the theoretical concepts of administrative leadership, their definition, foundations and patterns. As for the applied concepts, they were prepared using a questionnaire consisting of two axes (leadership styles and performance), distributed to 60 workers and analyzing their results using the SPSS program. Among the most important results reached, we found that there is a statistically significant relationship between the independent variables represented by administrative leadership styles and the dependent variable. It is the performance evaluation. As for the difference hypothesis, we found that there are no differences between the averages of the sample’s answers on the administrative leadership styles axis and the performance evaluation axis due to personal information. "
Keywords: القيادة الإدارية ، أنماط القيادة الإدارية ، تقييم الأداء. Administrative leadership; administrative leadership styles; performance evaluation.